Incidence of Viral Rebound After Treatment With Nirmatrelvir-Ritonavir and Molnupiravir - Grace Lai‐Hung Wong; Terry Cheuk‐Fung Yip; Mandy Sze‐Man Lai; Vincent Wai‐Sun Wong; David S.C. Hui; Grace Lui (2022)
Some patients treated with nirmatrelvir-ritonavir have experienced rebound of COVID-19 infections and symptoms; however, data are scarce on whether viral rebound also occurs in patients with COVID-19 receiving or not receiving molnupiravir.To examine the incidence of viral rebound in patients with COVID-19 who were treated with the oral antiviral agents nirmatrelvir-ritonavir and molnupiravir.This cohort study identified 41 255 patients with COVID-19 who were hospitalized from January 1, 2022, to March 31, 2022, in Hong Kong and assessed 12 629 patients with serial cycle threshold (Ct) values measured. Patients were followed up until the occurrence of the clinical end point of interest, death, date of data retrieval (July 31, 2022), or up to 30 days of follow-up, whichever came first.Molnupiravir or nirmatrelvir-ritonavir treatment.Viral rebound, defined as a Ct value greater than 40 that decreased to 40 or less.Of 12 629 patients (mean [SD] age, 65.4 [20.9] years; 6624 [52.5%] male), 11 688 (92.5%) were oral antiviral nonusers, 746 (5.9%) were molnupiravir users, and 195 (1.5%) were nirmatrelvir-ritonavir users. Compared with nonusers, oral antiviral users were older, had more comorbidities, and had lower complete vaccination rates. The mean (SD) baseline Ct value was slightly higher in nirmatrelvir-ritonavir users (22.2 [6.0]) than nonusers (21.0 [5.4]) and molnupiravir users (20.9 [5.4]) (P = .04). Viral rebound occurred in 68 nonusers (0.6%), 2 nirmatrelvir-ritonavir users (1.0%), and 6 molnupiravir users (0.8%). Among 76 patients with viral rebound, 12 of 68 nonusers, 1 of 6 molnupiravir users, and neither of the nirmatrelvir-ritonavir users died of COVID-19.In this cohort study, viral rebound was uncommon in patients taking molnupiravir or nirmatrelvir-ritonavir and was not associated with increased risk of mortality. Given these findings, novel oral antivirals should be considered as a treatment for more patients with COVID-19 in the early phase of the infection.